From UML activity diagrams to Stochastic Petri nets application to software performance engineering. - López-Grao, Juan Pablo (Software engineering notes.)
Over the last decade, the relevance of performance evaluation in the early stages of the software development life-cycle has been steadily rising. We honestly believe that the integration of formal models in the software engineering process is a must, in order to enable the application of wellknown, powerful analysis techniques to software models. In previous papers the authors have stated a proposal for SPE, dealing with several UML diagram types. The proposal for malizes their semantics, and provides a method to translate them into (analyzable) GSPN models. This paper focuses on activity diagrams, which had not been dealt with so far. They will be incorporated in our SPE method, enhancing its expressivity by refining abstraction levels in the statechart diagrams. Performance requirements will be annotated according to the UML profile for schedulability, performance and time. Last but not least, our CASE tool prototype will be introduced. This tool deals with every model element from activity diagrams and ensures an automatic translation from ADs into GSPNs strictly following the process related in this paper.